Addressing anhedonia to increase depression treatment engagement. (9th October 2021) - Khazanov, Gabriela K.; Forbes, Courtney N.; Dunn, Barnaby D.; Thase, Michael E.
Abstract : Anhedonia, or reward system dysfunction, is associated with poorer treatment outcomes among depressed individuals. The role of anhedonia in treatment engagement, however, has not yet been explored. We review research on components of reward functioning impaired in depression, including effort valuation, reward anticipation, initial responsiveness, reward learning, reward probability, and reward delay, highlighting potential barriers to treatment engagement associated with these components. We then propose interventions to improve treatment initiation and continuation by addressing deficits in each component of reward functioning, focusing on modifications of existing evidence‐based interventions to meet the needs of individuals with heightened anhedonia. We describe potential settings for these interventions and times at which they can be delivered during the process of referring individuals to mental health treatment, conducting intakes or assessments, and providing treatment. Additionally, we note the advantages of using screening processes already in place in primary care, workplace, school, and online settings to identify individuals with heightened anhedonia who may benefit from these interventions. We conclude with suggestions for future research on the impact of anhedonia on treatment engagement and the efficacy of interventions to address it. Practitioner points: Many depressed individuals who might benefit from treatment do not initiate it or discontinue early. One barrier to treatment engagement may be anhedonia, a core symptom of depression characterized by loss of interest or pleasure in usual activities. We describe brief interventions to improve treatment engagement in individuals with anhedonia that can be implemented during the referral process or early in treatment. We argue that interventions aiming to improve treatment engagement in depressed individuals that target anhedonia may be particularly effective.